The many faces of atypical haemolytic-uraemic syndrome: a diagnostic challenge - Chothia, Mogamat-Yazied; Coetzee, Liezel; Amirali, Mazhar Hussein (African Journal of Nephrology, 2019)
Atypical haemolytic-uraemic syndrome (aHUS) is a rare cause of thrombotic microangiopathy (TMA). The typical form occurs most frequently in children following infection with Shiga-like toxin-producing bacteria, whereas in the atypical form genetic mutations affecting complement regulatory proteins involved in the alternative complement pathway may be identified. The clinical features of aHUS may mimic other causes of TMA such as thrombotic thrombocytopenic purpura and malignant hypertension. We present a case of a 67-year-old woman who presented with a TMA and discuss the diagnostic challenges that were confronted due to the many overlapping clinical and laboratory features of the different causes of this syndrome. Clinicians should be aware of the varied clinical manifestations of TMAs to ensure early diagnosis and initiation of appropriate treatment.